ANALISIS KINERJA PROYEK UPSA SEBAGAI SUATU STRATEGI REHABILITASI LABAN KRITIS DI DAERAH ALIRAN SUNGAI SOLO, JAWA TENGAH - Hariyatno Dwiprabowo; Kirsfianti Linda Ginoga (Jurnal Penelitian Hasil Hutan, 1995)
This report reviews the role of UPSA project as a strategy for rehabilitation of critical land in Solo Watershed Area, Central Java. In particular, status identification of critical land and UPSA's performance, are examined. UPSA (Unit Percontohan Sumberdaya Alam) or demonstration plot for natural resources sustainability, is funded and managed by Directorate General of Reforestation and Land Rehabilitation, Ministry of Forestry, through Sub Centre for land Rehabilitation and Soil Conservation of Solo (Sub Balai Rehabilitasi Lahan dan Konservasi Tanah, Sub BRLKT Solo).Based on critical land status, the main critical land found in research site is hydrologically critical (80,5%), followed by productively critical (19,5%). The status is determined qualitively based on information gained from the field.The technical performance of UPSA was reviewed on the basis of three criteria, i.e., pro- ductivity, sustainability and equitability. The indicators examined suggested that productivity had been enhanced, though not the case for sustainability. UPSA appears to be profitable for participating farmers. Although the actual surpluses gained by some farmers are not very high.